Ustanowienie świętego patrona miast, gmin, powiatów i województw - Świderski, Krzysztof (Studia Prawa Publicznego, 2022)
The subject of this article is the procedure for selecting a saint of the Roman Catholic Church patron saint for the city, municipality or wider territory. The establishment of a patron saint is within the competence of the confessional authority, in particular, the bishop and the Congregation for Divine Worship and the Discipline of the Sac-raments. The procedure consists of three stages: the election, acknowledgement and affirmation of the patron saint. The church’s current regulations regarding the election of patron saints are contained in two documents of the Holy See. The municipal council, the poviat council and the assembly of the province pass a res-olution on the patron at the stage of his election by the society and the clergy. The above-mentioned authorities do not take part in the next two stages. Entities of territorial self-government only have a supporting vote. They cannot independently establish a patron saint, regardless of the decisions of the ecclesiastical authorities. The position of administrative courts that the resolutions of the constitutive au-thorities of entities of territorial self-government belong to the category of public administration matters is unjustiﬁed. The decree of the Congregation for Divine Worship and the Discipline of the Sacraments is addressed to a given diocese and not to local self-government authorities. The patron saint is established for a city, mu-nicipality, poviat, or for an area that does not have administrative borders. Entities of territorial self-government must respect the autonomy of the church authorities, and public authorities should be impartial in religious matters. Therefore, entities of territorial self-government do not have the competence to establish a patron saint for the promotion of a municipality, district or self-government of the voivodship. However, they can refer to saint persons at the symbolic level, for example, in the coat of arms or the names of streets and squares. This also applies to schools and hospitals run by local self-government authorities.